2020
DOI: 10.1515/chem-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent growth kinetics of struvite crystals in wastewater with calcium ions

Abstract: AbstractKinetic parameters describing continuous reaction crystallization of struvite from aqueous solutions containing also calcium ions (from 100 to 2000 mg Ca2+/kg) were estimated. Test results were compared with kinetic data of struvite manufactured from real cattle liquid manure. Kinetic model for ideal MSMPR (Mixed Suspension Mixed Product Removal) crystallizer was used assuming dependence of crystal growth rate G on its siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…26 Unfortunately, these conditions are not found in actual HTL-AP product effluents, which contain significant concentrations of foreign ions and polar organic compounds, 7,25,27 higher ionic strength (0.2−0.4 M), 25,28 and nonequimolar Mg/NH 3 −N/P ratios. 29−32 Few studies have investigated the struvite crystallization thermodynamics and kinetics in real wastewaters, adopting different kinetic models, e.g., linear growth rate, 33 first-order kinetics, 26 population balance, 34 and size-dependent growth 35 models. To design a fluidized bed reactor for struvite production, a recent study 36 proposed three solid−liquid flow models, i.e., complete mixing of liquid and bed, plug flow of liquid and perfect classification of the bed, and plug flow of liquid and complete mixing of the bed, incorporated with reduced thermodynamic and growth kinetic models; the aim of the study was to improve previously proposed flow models by Rahaman et al 37 and Burns et al 38 However, those studies assume an ideal condition, neglecting the change of chemical thermodynamic properties at different temperatures and pH, e.g., ionic strength and effective concentration or activity of the reacting ions, during crystallization and the possibility of side reactions caused by foreign ions, e.g., hydroxyapatite formation due to Ca 2+ presence.…”
Section: Introductionmentioning
confidence: 99%
“…26 Unfortunately, these conditions are not found in actual HTL-AP product effluents, which contain significant concentrations of foreign ions and polar organic compounds, 7,25,27 higher ionic strength (0.2−0.4 M), 25,28 and nonequimolar Mg/NH 3 −N/P ratios. 29−32 Few studies have investigated the struvite crystallization thermodynamics and kinetics in real wastewaters, adopting different kinetic models, e.g., linear growth rate, 33 first-order kinetics, 26 population balance, 34 and size-dependent growth 35 models. To design a fluidized bed reactor for struvite production, a recent study 36 proposed three solid−liquid flow models, i.e., complete mixing of liquid and bed, plug flow of liquid and perfect classification of the bed, and plug flow of liquid and complete mixing of the bed, incorporated with reduced thermodynamic and growth kinetic models; the aim of the study was to improve previously proposed flow models by Rahaman et al 37 and Burns et al 38 However, those studies assume an ideal condition, neglecting the change of chemical thermodynamic properties at different temperatures and pH, e.g., ionic strength and effective concentration or activity of the reacting ions, during crystallization and the possibility of side reactions caused by foreign ions, e.g., hydroxyapatite formation due to Ca 2+ presence.…”
Section: Introductionmentioning
confidence: 99%
“…This model is based on the population balance equation. It is a method used to estimate the kinetic parameters of the crystallization of struvite, which depend on the crystal size distribution (CSD) of the product [ 17 , 25 , 26 ]. The crystal growth rate and nucleation rate affect CSD in solution, which is the key to control the quality of struvite [ 27 ].…”
Section: Model Of Struvite Crystallizationmentioning
confidence: 99%
“…In a study conducted by Hutnik et al [ 26 ], the SDG model was used to determine how calcium ions affect the crystallization of struvite. When the concentration of calcium ions was increased from 100 mg/L to 2000 mg/L, the nuclear growth rate decreased significantly from 2.30 × 10 −11 to 2.09 × 10 −12 m/s.…”
Section: The Parameters That Influence Struvite Crystallizationmentioning
confidence: 99%
“…The size attained by struvite crystal during product precipitation depends on a two-step process: nucleation and crystal growth. The growth of the crystal is affected by a combination of several factors such as the pH (Matynia et al 2006), supersaturation, mixing turbulence (Matynia et al 2006), and presence of foreign ions (Le et al 2005;Liu & Wang 2019;Moragaspitiya et al 2019;Hutnik et al 2020). Le et al (2005) found that at higher concentrations of Ca (with regard to Mg) in the solution, the mean size of the struvite is decreased.…”
Section: Crystal Sizementioning
confidence: 99%
“…The presence of Ca 2þ during struvite precipitation has been shown to negatively affect characteristics of the struvite produced (Le et al 2005Liu & Wang 2019;Moragaspitiya et al 2019;Bayuseno & Schmahl 2020;Hutnik et al 2020). Precipitating struvite at high Ca concentration produces undesired amorphous product and reduces the proportion of P in the struvite (Desmidt et al 2013;Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%